More Evidence on the Performance of Merger Simulations - Weinberg, Matthew C (American Economic Review, 2011)
Merger simulations are commonly used to simulate the effects of potential mergers. Despite the large resources devoted to merger review, little evidence exists on the accuracy of these methods. This paper uses the acquisition of Tambrands by Proctor and Gamble to provide evidence on the efficacy of merger simulation. Two simple demand systems are estimated under several identification assumptions and combined with a static model of price competition. Simulations predict small price effects of about 1 percent for the merging firms' brands, while direct estimates indicate the merger raised prices by 5–8 percent.